Biocompatibility in Ternary Fermentations With Lachancea thermotolerans, Other Non-Saccharomyces and Saccharomyces cerevisiae to Control pH and Improve the Sensory Profile of Wines From Warm Areas - Vaquero, Cristian; Loira, Iris; Heras, José María; Carrau, Francisco; González, Carmen; Morata, Antonio (Frontiers in Microbiology, 2021)
Global warming is causing serious problems, especially in warm regions where musts with excess sugars and high pH produce wines with decreased freshness and unstable evolution. This study aimed to determine biocompatibility between yeast species, the capacity for microbiological acidification, and the aromatic profile produced in ternary fermentations in which Lachancea thermotolerans has been co-inoculated with Hanseniaspora vineae, Torulaspora delbrueckii, or Metschnikowia pulcherrima and the fermentation process is subsequently completed with sequential inoculation of Saccharomyces cerevisiae. For this purpose, different cell culture media and instruments were used, such as infrared spectroscopy, enzymatic autoanalyzer, chromatograph coupled with a flame ionization detector, spectrophotometric analysis, among others. The behavior of these yeasts was evaluated alone and in co-inoculation, always finishing the fermentation with sequential inoculation of S. cerevisiae, at a stable temperature of 16°C and with a low level of sulfites (25mg/L) in white must. Significant results were obtained in terms of biocompatibility using population counts (CFU/mL) in differential plating media that permitted monitoring. Quantification of the five species was studied. Concerning acidification by L. thermotolerans in co-inoculations, we showed some metabolic interactions, such as the inhibition of acidification when Hvineae/Lthermotolerans were used, generating just over 0.13g/L of lactic acid and, conversely, a synergistic effect when Mpulcherrima/Lthermotolerans were used, achieving 3.2g/L of lactic acid and a reduction in pH of up to 0.33. A diminution in alcohol content higher than 0.6%v/v was observed in co-inoculation with the Lthermotolerans/Mpulcherrima yeasts, with total sugar consumption and very slow completion of fermentation in the inoculations with H. vineae and T. delbrueckii. The aromatic composition of the wines obtained was analyzed and a sensory evaluation conducted and it was found that both L. thermotolerans and co-inoculations retained more aromatic esters over time, had a lower evolution towards the yellow tones typical of oxidation and that the best sensory evaluation was that of the Lt+Mp co-inoculation. L. thermotolerans and co-inoculations all produced wines with low levels of volatile acidity (<0.4g/L). This work shows that good consortia strategies with binary and ternary fermentations of yeast strains can be a powerful bio-tool for producing more complex wines.